Multiwavelength single cavity Brillouin Erbium Fiber Laser (BEFL) / Mariasuzila Mahadi - Mahadi, Mariasuzila (2008)
This project focuses on how Multiwavelength Single Cavity Brillouin Erbium Fiber Laser (BEFL) can improve Brillouin stokes signal in the system by using 500m of SMF. The objectives of this project are to characterize optical components, design and set up of multiwavelength single cavity BEFL system and also to characterize and test BEFL system. Significance of this project is to increase the Brillouin stokes by using BEFL system. This is because in telecommunication system, Brillouin is a special gain medium that function to increase the number of Brillouin stokes signal. This system also can produce multiple wavelengths simultaneously by using one light source. Scope for these projects covers identifying and characterizes the optical component that will be used in designing multiwavelength single cavity Brillouin Erbium fiber laser, an efficiency of multiwavelength single cavity Brillouin Erbium fiber laser and also the number of Brillouin Stokes signal. The process of understanding of BEFL system and demonstrating this system is very important to achieve the objectives of this project. Maximum of 9 Brillouin stokes was able to achieve by increasing SMF pump power until 3mW. However, when the SMF pump power was increased until its maximum power 9mW, the Brillouin stokes will decrease.